Single-Port Subcostal Robot-Assisted Minimally Invasive Esophagectomy—How to Do It? - Hadzijusufovic, Edin; Lozanovski, Vladimir J.; Bellaio, Luca; Tagkalos, Evangelos; Uzun, Eren; Griemert, Eva-Verena; Lang, Hauke; Grimminger, Peter P. (The Thoracic and Cardiovascular Surgeon, 2025)
Minimally invasive robot-assisted esophagectomies have proven superior to traditional open surgery. While transhiatal and transthoracic approaches are common, subcostal access remains less frequent in minimally invasive esophageal surgery. Recent advancements in robotic systems, such as the da Vinci Single-Port (SP), now facilitate precise subcostal access. This innovation holds potential to reduce postoperative pain, enhance patient mobility, and broaden surgical options for patients with multiple health conditions. The Single-Port Subcostal Robot-Assisted Minimal Invasive Esophagectomy (SP SC RAMIE) utilizes an SP and laparoscopic approach, enabling effective mediastinal dissection and esophageal mobilization with radical lymphadenectomy. This novel technique shows promise, especially for frail patients with multiple comorbidities who stand to benefit greatly from expedited recovery pathways. Nonetheless, further exploration is necessary to fully assess its clinical effectiveness and reproducibility.
Keywords: minimally invasive surgery; robotic; esophageal surgery